Real Time Factory Smokes Monitoring System Using Android Smartphone - Moch Andreyan Adi Prakoso; Lusia Rakhmawati (Department of Electrical Engineering, Faculty of Engineering, Universitas Negeri Surabaya, 2021)
Owing to widespread deforestation and the rapid growth of modern plants, we can see and experience a lot of air that is no longer what it once was. Carbon Monoxide (CO), which is generated by residual combustion in industrial plants and emitted through factory chimneys, is one of the factors that contribute to air pollution. This study was designed to help the government monitor Carbon Monoxide (CO) levels more efficiently because it can be done at any time in real time using an Android smartphone's media. Furthermore, this research is being conducted to develop simple technology that can be used by parties who need or have an interest in monitoring Carbon Monoxide (CO) levels as well as reducing the number of emissions in the local area. The results showed that the MQ-7 sensor on the monitoring tool could detect carbon monoxide levels accurately and had a 0.72 percent error rate when retrieving data several times. The CO meter's sensitivity is equivalent to that of an NDIR (Non-Dispersive Infrared Detector) Analyzer, which is commonly used for measuring and detecting carbon monoxide levels in the air. These findings suggest that this instrument can be used to better monitor carbon monoxide (CO) levels in the air.